Cardioprotective effects of PCSK9 inhibitor evolocumab against doxorubicin-trastuzumab sequential treatments and ipilimumab-induced cardiotoxicity: the role of MyD88/NF-KB/mTORC1 pathways. (25th November 2020) - Quagliariello, V; Caronna, A; Lombari, C; Bonelli, A; Conforti, G; Botti, G; Maurea, N
Abstract: Introduction: Inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a novel therapy to treat hypercholesterolaemia and related cardiovascular diseases. Evolocumab, a PCSK9 inhibitor, reduced the risk of cardiovascular events in patients with atherosclerotic cardiovascular diseases when added to maximally tolerated statin therapy (± ezetimibe), and recent data from the ODYSSEY OUTCOMES trial indicate that alirocumab added to maximally tolerated statin therapy (± other lipid-lowering drugs) reduces the risk of cardiovascular events in patients with a recent acute coronary syndrome. Purpose: Considering the expression of PCSK9 in heart tissue, we aimed to study for the first time the direct biochemical effects of evolocumab in cardiomyocytes during exposure to doxorubicin, trastuzumab, their sequential treatments, and immune checkpoint inhibitor ipilmumab. Methods: Human fetal cardiomyocytes (HFC cell line) were exposed to subclinical concentration of doxorubicin, trastuzumab, sequential treatment of both ( all 100 nM), alone or in combination with evolocumab (50 nM) for 48h. In another experiment, in co-coltures of human fetal cardiomyocytes and lymphocytes, we incubated ipilimumab (200 nM) alone or in combination with evolocumab for 48h. After the incubation period, we performed the following tests: determination of cell viability, through analysis of mitochondrial dehydrogenase activity, study of lipid peroxidation (quantifying cellular Malondialdehyde and 4-hydroxynonenal), intracellular Ca2+ homeostasis. Moreover, pro-inflammatory studied were also performed (activation of NLRP3 inflammasome; expression of TLR4/MyD88; mTORC1 Fox01/3a; transcriptional activation of p65/NF-κB and secretion of cytokines involved in cardiotoxicity (Interleukins 1β, 8, 6). Results: Evolocumab co-incubated with doxorubicin alone or in sequence with trastuzumab exerts cardioprotective effects, enhancing cell viability of 35–43% compared to untreated cells (p<0, 05 for all); Cardiomyocytes co-incubated withevolocumab and ipilimumab (in co-colture of cardiomyocytes and lymphocytes) reduces significantly the cardiotoxicity phenomena through MyD88/NF-KB/cytokines axis and mTORC1 Fox01/3α mediated mechanisms. Conclusion: We demonstrated, for the firts time, that PCSK9 inhibitor evolocumab exerts direct effects in cardiomyocytes during doxorubicin, trastuzumab and ipilimumab mediated cardiotoxicity turning on a new light on its possible use in the management of the cardiotoxic effects of antineoplastic drugs in cancer patients Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): This work was funded by the "Ricerca Corrente" grant from the Italian Ministry of Health